ANALISIS PENGARUH PEMADAMAN LISTRIK SECARA BERKALA SERTA PENGGUNAAN GENSET TERHADAP KEGIATAN USAHA MIKRO DI KECAMATAN MEDAN BARU - Ira Destiana Pasaribu; Raina Linda Sari (Departemen Ekonomi Pembangunan USU, 2014)
This study purpose to analyze the effect of periodically power outage and using generators on revenues micro enterprises in the District of Medan Baru.The data used is primary, data obtained from the questionnaires to micros businesses as many as 25 respondents who use generators and 25 micro-businesses that do not use generators. In this study the use of generators using dummy variables. Data analysis method used is multiple regression with SPSS tools 19 .From the regression results indicate that the effect of periodically power outage on revenue equal to –253130,865 and the effect of using generators on revenue equal to –1,0696.Keywords : Periodically Power Outage, Revenue, Generator